The relationship between product cues, attitude towards brand and purchase intention of automobiles - Hashim, Noor Azmi; Mohammad, Osman; Mustafa, Munauwar (2011)
The varying characteristics reflective of the actual diversity in how intentions are conducted have found that intentions are significantly better predictors of purchase behavior for existing products and for durable than for non-durable products. These results are remarkable because in practice, intentions are often used to predict sales for new non-durable products and also that intentions are better predictors of behaviors over short that over long time horizons. Branding is also important because it communicates a brand's business proposition. The most successful visual expression of a brand is its core attributes and it needs to establish a positive emotional relationship between the brand and its audiences. Building a local, regional, or national brand with a clearly defined and understood target audience is difficult and even more difficult when a global brand is at stake. Some global brands are strongly associated with their country of origin.In certain categories, this is part of the essence of the brand. Automobiles are the most notable examples. The objective of this study is to understand the variable influencing consumers' purchase intention related to automobiles. In particular, this study provides an insight into the perception of Malaysian consumers with regards to their purchase intention of a certain brand of automobiles.